Prognosis of Paradoxical Low-Flow Low-Gradient Aortic Stenosis: A Severe, Non-critical Form, With Surgical Treatment Benefits - Galian-Gay, Laura; Escalona Silva, Roxana Andreina; Teixidó-Turà, Gisela; Casas, Guillem; Ferrer-Sistach, Elena; Mitroi, Cristina; Mingo, Susana; Monivas, Vanessa; Saura, Daniel; Vidal, Bàrbara; Trasca, Livia; Moral, Sergio; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives To determine the risk of mortality and need for aortic valve replacement (AVR) in patients with low-flow low-gradient (LFLG) aortic stenosis (AS). Methods A longitudinal multicentre study including consecutive patients with severe AS (aortic valve area [AVA] < 1.0 cm2) and normal left ventricular ejection fraction (LVEF). Patients were classified as: high-gradient (HG, mean gradient ≥ 40 mmHg), normal-flow low-gradient (NFLG, mean gradient < 40 mmHg, indexed systolic volume (SVi) > 35 ml/m2) and LFLG (mean gradient < 40 mmHg, SVi ≤ 35 ml/m2). Results Of 1,391 patients, 147 (10.5%) had LFLG, 752 (54.1%) HG, and 492 (35.4%) NFLG. Echocardiographic parameters of the LFLG group showed similar AVA to the HG group but with less severity in the dimensionless index, calcification, and hypertrophy. The HG group required AVR earlier than NFLG (p < 0.001) and LFLG (p < 0.001), with no differences between LFLG and NFLG groups (p = 0.358). Overall mortality was 27.7% (CI 95% 25.3–30.1) with no differences among groups (p = 0.319). The impact of AVR in terms of overall mortality reduction was observed the most in patients with HG (hazard ratio [HR]: 0.17; 95% CI: 0.12–0.23; p < 0.001), followed by patients with LFLG (HR: 0.25; 95% CI: 0.13–0.49; p < 0.001), and finally patients with NFLG (HR: 0.29; 95% CI: 0.20–0.44; p < 0.001), with a risk reduction of 84, 75, and 71%, respectively. Conclusions Paradoxical LFLG AS affects 10.5% of severe AS, and has a lower need for AVR than the HG group and similar to the NFLG group, with no differences in mortality. AVR had a lower impact on LFLG AS compared with HG AS. Therefore, the findings of the present study showed LFLG AS to have an intermediate clinical risk profile between the HG and NFHG groups.